The Henry Reaction Efficiently Catalyzed by a Cd-Proline Complex - Wang, Junke; Lu, Zhi-Jin; Wang, Le-Yong; Bai, Junfeng; Pan, Yi (Letters in Organic Chemistry, 2008)
The Henry reaction has been efficiently catalyzed by a Cd-proline complex in water at ambient temperature to afford the β-nitroalcohols in good to excellent yields. Effective recovery and recycling (up to five runs) of the catalyst are documented.
Keywords: henry reaction